Performance Evaluation of Guidance and Counseling Teachers: Guidance and Counseling Service Management in an Islamic Perspective - Agus Saeful Anwar; Abdus Salam DZ; Iman Subasman; Maftuhah Dewi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to evaluate the performance of guidance and counseling (BK) teachers in managing BK services based on an Islamic perspective at SMK Karya Nasional Kuningan, as well as to identify the effectiveness and challenges of its implementation. The research method employed was a mixed-methods approach, combining in-depth interviews, participatory observation, and quantitative surveys with a 5-point Likert scale questionnaire completed by 150 students and 30 teachers. The results of the study indicate that BK services have been effective in meeting students' needs in character development and understanding Islamic moral values, such as honesty and responsibility. Quantitative evaluation reveals a significant correlation between the integration of Islamic values and student satisfaction with the services. However, challenges were also identified, including gaps in understanding Islamic values, limited teacher training, and negative stigma towards BK services, which hinder the optimization of the program. The implications of this study emphasize the importance of enhancing BK teacher training, socializing Islamic values to students and parents, and providing sustained institutional support to improve the effectiveness of BK services. The findings contribute to the development of holistic and adaptive religion-based counseling services within an Islamic perspective.